2023
DOI: 10.3390/foods12030580
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Wheat Bread with Platycodon grandiflorus Root (PGR) Flour: Rheological Properties and Microstructure of Dough and Physicochemical Characterization of Bread

Abstract: Platycodon grandiflorus (Jacq.) A.DC. root (PGR) flour is well known for its medical and edible values. In order to develop nutritionally fortified products, breads were prepared using wheat flour, partially replaced with PGR flour. The rheological properties and microstructure of dough and the physicochemical characterization of bread were investigated. Results showed that lower level of PGR addition (3 and 6 g/100 g) would improve the baking performance of breads, while the higher level of PGR addition (9 g/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…These findings suggested that adding S-RBDF to naan could contribute to the retention and sustained release of red date flavor compounds. This result was mainly attributed to the fact that S-RBDF has an unfolded structure and a large specific surface area, exposing more internal active binding sites, which contribute to the adsorption of flavor compounds and inhibits their diffusion in the interlayer space ( Liu et al, 2023 ). Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggested that adding S-RBDF to naan could contribute to the retention and sustained release of red date flavor compounds. This result was mainly attributed to the fact that S-RBDF has an unfolded structure and a large specific surface area, exposing more internal active binding sites, which contribute to the adsorption of flavor compounds and inhibits their diffusion in the interlayer space ( Liu et al, 2023 ). Fig.…”
Section: Resultsmentioning
confidence: 99%
“… Identification methods: RI: retention index; MS: mass spectra data; Std: confirmed by authentic standards. Odor descriptions were obtained from the literature ( He et al, 2023 ; Liu et al, 2023 ). Values are mean ± standard deviation (n = 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the muscle specific volume illustrates the skeletal muscle volume in different individuals 12 . In the food field, the bread specific volume width indicated the fluctuation of the expanded bread volume with the same mass 16,17 at various conditions. In chemistry, liquid specific volumes emphasize the volume fluctuation 18 with the same mass at different temperatures.…”
Section: Calculation Of Hswmentioning
confidence: 99%
“…These properties generally reflect the type and quantity of recipe ingredients or technology modifications. This is particularly visible in the analysis of viscoelastic properties, which affect the quality of the resulting bread, mainly the volume of the loaves and the texture of the crumb [ 2 ]. In addition, there are other reasons why the rheological properties of dough are important.…”
Section: Introductionmentioning
confidence: 99%